Determinants of the accounting information system and its role in reducing tax evasion cases (A field study in the tax departments in Sulaymaniyah Governorate) - Hardi Azad Omer (The Scientific Journal of Cihan University– Sulaimaniya, 2019)
Tax evasion is interwined and intervened with money laundering and corruption. One of the main reasons that led this phenomenon to prosper rapidly is referes to the weaknesses in the role of accounting information system and various technological development, particularly in the field of paying tax and raising money. The main objective of this research is to illustrate the role and effect of accounting information system on providing financial reports, which reduce the case of tax evasion. To achieve the objective of the research, descriptive-analytical approach has been conducted, via collecting relevant data on distributed questionnaires among government employees with various expertise in Sulaimani. Finally, research reached several conclusions, for instance; the determinante of accounting information system has an obvious impact on building an intellectual and conceptual framework on the system, which could impact on tax evasoion circumstances. Moreover, tax entities in Kurdistan Region – Iraq seeks to find a rules and instruction in order to reduce the level of tax evasion. Based on this, it is significant combat against this issue through using a recent methods and approaches in the area of accounting information system as well as getting benefits from other countries experiences to limit tax evasion by creating an accomplished and active accounting information system.